Alternating direction method for a two‐dimensional parabolic equation with a nonlocal boundary condition - Sapagovas, Mifodijus; Kairytė, Gene; Štikonienė, Olga; Štikonas, Artūras (Mathematical Modelling and Analysis, 2007)
The present paper deals with an alternating direction implicit method for a two dimensional parabolic equation in a rectangle domain with a nonlocal boundary condition in one direction. Sufficient conditions of stability for Peaceman‐Rachford method are established. Results of some numerical experiments are presented. First Published Online: 14 Oct 2010